2007
DOI: 10.1111/j.1440-1819.2007.01614.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Japanese version of the Frontal Assessment Battery in patients with the frontal variant of frontotemporal dementia

Abstract: Patients with the frontal variant of frontotemporal dementia (fv-FTD) exhibit deficits of executive functions. However, no single executive function task that might be used to detect the executive function deficits in fv-FTD patients has been established as yet. The frontal assessment battery (FAB) devised by Dubois et al. (2000) has been reported to be a quick and simple bedside screening test that is sensitive for differentiating between FTD and Alzheimer's disease (AD). The present study was conducted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 21 publications
1
40
0
Order By: Relevance
“…On the other hand, the test-retest reliability of the TFAB was good, and this result confirmed the findings of previous studies (Appollonio et al, 2005;Dubois et al, 2000;Kim et al, 2010;Kugo et al, 2007;Mok et al, 2004;Nakaaki et al, 2007). For example, Kim et al (2010) examined healthy participants to assess the reliability of the KFAB and found good test-retest reliability (r ¼ .82, p < .001).…”
Section: Psychometric Properties Of the Tfabsupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, the test-retest reliability of the TFAB was good, and this result confirmed the findings of previous studies (Appollonio et al, 2005;Dubois et al, 2000;Kim et al, 2010;Kugo et al, 2007;Mok et al, 2004;Nakaaki et al, 2007). For example, Kim et al (2010) examined healthy participants to assess the reliability of the KFAB and found good test-retest reliability (r ¼ .82, p < .001).…”
Section: Psychometric Properties Of the Tfabsupporting
confidence: 91%
“…For example, the internal consistency of the FAB has been evidenced as fair (Dubois et al, 2000) when evaluating a larger sample of patients with frontal lesions. A recent study from Japanese researchers (Nakaaki et al, 2007) revealed that the internal consistency of the FAB was also fair when examining patients with frontotemporal dementia. In an Italian population, Appollonio et al (2005) recruited 364 healthy participants who were aged 20 to 94 years old.…”
Section: Introductionmentioning
confidence: 98%
“…A previous study reported similar results [14] . Although prehension behavior is reportedly useful in discriminating other types of dementia, such as frontotemporal dementia [12,16,17,20] and vascular dementia [18] from normal elders, it may not be suitable for the early detection of dysexecutive syndrome in AD due to this ceiling effect [14] . Therefore, Mok et al [15] suggested that prehension behavior should be replaced by other brief executive tests.…”
Section: Discussionmentioning
confidence: 99%
“…A higher score means a better performance, and the maximum possible sum of the scores is 18 (scores on each item range from 0 to 3). The FAB's reliability and validity have been demonstrated by studies of various neurodegenerative diseases [15][16][17][18][19][20] , and FAB score has been correlated with the blood flow in the frontal lobe [21] . The FAB provides as much information about the presence of executive dysfunction as the EXIT-25 can [22] but takes less time to complete and is less frustrating for patients.…”
mentioning
confidence: 99%
“…For this study, we used the Japanese version of the FAB described by Kugo et al [10] . The reliability of the Japanese version of the FAB is good to excellent, and its validity is, to some extent, established [9,10] .…”
Section: The Instrumentmentioning
confidence: 99%